Cultura e o clima organizacional, o real e o ideal, nas Delegacias da Polícia Federal - Carmo, Eliane Rodrigues do (2017)
This study investigated the real and ideal of culture and organizational climate within the Federal Police Stations. The study is justified by the few studies conducted within the Federal Police Department, and this was the first to be authorized on the southern border of Brazil. Police organizations have specific culture and characteristics that affect the management of this type of organization. The study was descriptive of qualitative and quantitative, with crosssection, without considering the evolution of data in time. The instruments of data collection were two questionnaires. The first evaluated the climate with seven factors: conformism, responsibility, standards, rewards, organizational clarity, support and warmth and leadership. The other evaluated the organizational culture with 21 questions. Both use the Likert scale with weights from 1 to 10 on a frequency scale. The population studied was of the police stations of Cascavel, Guaíra and Foz do Iguaçu, totaling 182 people. The data were treated by descriptive statistics and analyzed descriptively. The results showed that the predominant factors in analyzing the differences in gender-based assessments were that there was a greater divergence in assessing the desired situation, both in the climate and in the organizational culture. It is noteworthy that the male sex presented greater evaluations regarding the desired situation. The results the results showed great divergence, between real or perceived level and the ideal or desired, in all the factors of the climate and the organizational culture.